Screening Protocol for Early Identification of Brazilian Children at Risk for Dyslexia - Germano, Giseli D.; César, Alexandra B. P. de C.; Capellini, Simone A. (Frontiers in Psychology, 2017)
Early identification of students at risk of dyslexia has been an educational challenge in the past years. This research had two main goals. First, we aimed to develop a screening protocol for early identification of Brazilian children at risk for dyslexia; second, we aimed to identify the predictive variables of this protocol using Principal Component Analysis. The major step involved in developing this protocol was the selection of variables, which were chosen based on the literature review and linguistic criteria. The screening protocol was composed of seven cognitive-linguistic skills: Letter naming; Phonological Awareness (which comprises the following subtests: Rhyme production, Rhyme identification, Syllabic segmentation, Production of words from a given phoneme, Phonemic Synthesis, and Phonemic analysis); Phonological Working memory, Rapid naming Speed; Silent reading; Reading of words and nonwords; and Auditory Comprehension of sentences from pictures. A total of 149 children, aged from 6 years to 6 and 11, of both genders who were enrolled in the 1st grade of elementary public schools were submitted to the screening protocol. Principal Component Analysis revealed four factors, accounting for 64.45% of the variance of the Protocol variables: first factor (“pre-reading”), second factor (“decoding”), third factor (“Reading”), and fourth factor “Auditory processing”. The factors found corroborate those reported in the National and International literature and have been described as early signs of dyslexia and reading problems.